Peningkatan Hasil Belajar Menghitung Dana Kas Kecil Melalui Model Pembelajaran Langsung Dengan Pendekatan Problem Posing (Pendidikan Ekonomi, 2013)
The purpose of this research is to know  the  increasing of  learning outcomes in petty cash counting, to know the activity of  teacher and student by applying direct learning model with problem approach of class X accounting 2 in SMK Negeri 1 Tarakan, second semester of academic year 2013/2014. This type of research is classified in classroom action research (CAR) by applying direct learning model with problem posing approach. The instrument for collect data consist of observation, documentation and test. Data analysis use descriptive analysis and qualitative analysis consist of analysis items, analysis of teacher’s activity, student’s activity analysis and outcomes learning’s analysis.  The result of analysis showed fluctuating in good category , observation of teacher activity in cycle 1 was 3.8% , cycle 2 was 3.7% , cycle 3 was  3.9 %  while in observation of student activity in cycle 1 was 3.8% , cycle 2 was 3.7% and cycle 3 was  3.9%.  Classical completeness in cycle 1 was 94 % , cycle 2 was 88%  and cycle 3 was 97 %.  Based on the result of this research is concluded that, the direct learning model by problem posing approach eligible to improvement of student learning outcomes in petty cash counting . Key words: Direct learning model, problem posing and outcomes learning